Medico-legal problems regarding self-disposition of one’s own body - Fiori, Angelo; Pascali, Vincenzo; Marchetti, Daniela (Medicina e Morale, 1991)
The Authors think that there are some particular aspects of medicai therapeutic treatment, expecially those which concem irreversible sterilization, sex changes and terminai illness, that require considerations about the aim and the bounderies of medicai science. For this reason the authors focused first of all on the resulting permanent impairment and then on a criticai analysis of the impartance of the patient's consent and its relationship with that of the community.